Excessive Daytime Sleepiness Measurements in Children With Attention Deficit Hyperactivity Disorder - Bioulac, Stéphanie; Taillard, Jacques; Philip, Pierre; Sagaspe, Patricia (Frontiers in Psychiatry, 2020)
Abstract Attention deficit hyperactivity disorder (ADHD) is the most commonly diagnosed neurodevelopmental disorder in childhood. It is a heterogeneous disorder in terms of clinical presentation that is probably due to the frequent occurrence of comorbidity. Children with ADHD more frequently report sleep disorders (notably delayed sleep phase syndrome) and excessive daytime sleepiness (EDS) than typically developing children. The aim of this article is to propose an overview of the assessment of EDS in the context of ADHD with first a summary of subjective and objective tools used. While subjective assessments evidence EDS, data for objective tools are limited and heterogeneous. Some specific clinical situations associating EDS and ADHD are demonstrated, such as links with narcolepsy and the existence of a specific phenotype: “narcolepsy-like ADHD” or “sleepiness ADHD”. Then, perspectives in terms of electroencephalogram markers (EEG) and neuro-cognitive evaluation are presented and how these kinds of biomarkers can help to better phenotype patients with ADHD. EDS, a symptom that is objectively measurable, may be a key factor in better evaluating these patients and offering specific treatment that may be pharmacological or non-pharmacological, such as neurofeedback.